Risk Mitigation Strategy for CNC Plasma Cutting Machine Damage Using The House of Risk Method and Root Cause Analysis - Aryaduta, Galang; Rusindiyanto, Rusindiyanto (Newinera Publisher, 2025)
PT XYZ as a national strategic industrial company has a high dependence on the reliability of production machines, one of which is the CNC Plasma Cutting machine. Damage problems that occur on the machine can disrupt the smooth production process and pose a significant operational risk. In 2024, this machine experienced 35 breakdowns which resulted in a decrease in plate cutting output from the target of 1560 tons to 1417 tons. This study aims to identify the risk of machine failure and formulate mitigation strategies using the House of Risk (HOR) and Root Cause Analysis (RCA) methods. HOR is used to identify risk events, risk agents, and determine mitigation priorities based on the Aggregate Risk Potential (ARP) value, while RCA is used to find the main root cause of selected risks. The results showed that there were 5 mitigation actions that could potentially increase the cutting output by 8.8%, from 1417 tons to 1542 tons in 12 months. The combination of the HOR and RCA methods provides a comprehensive approach to risk mitigation, supporting the achievement of the slaughter output target.